Penerapan Model Pembelajaran Tipe Kooperatif Team Assistend Individualization (TAI) untuk Meningkatkan Prestasi Belajar Siswa - Suparti Suparti (Academy of Education Journal, 2018)
In learning activities there are many factors that determine learning success, not only from students, but also from the teacher and the learning methods used. Submission of boring material will make many students unmotivated in the learning process so as to make learning outcomes / learning achievements low, this also happens in SDN Kalisube Class Vl Semester I 2016/2017 school year. To increase students' motivation and learning achievement, the teacher applies and uses the Team Assisted Individualization (TAI) Cooperative learning model in the Science Basic Competency map comparing the nature of the ability to conduct heat from various objects. The study was divided into two cycles.After conducting research the results obtained by students are, in the initial study showed only 3 children or 15% of 20 students. completed learning, this is far above the established criteria that is a minimum of 90% of students completed from the total number of students, in cycle I there were 65% or 13 students who completed, cycle 2 there were 100% or 20 students who had already completed study, the average value obtained in the initial study 62 and in the first cycle increased to 75 in the second cycle an average value of 87.Judging from the acquisition of learning outcomes can be interpreted that the Learning Model Cooperative learning model Type Team Assisted Individualization (TAI) has a positive impact on the learning process. Students are more motivated to learn, more active and mastery learning increases. Thus the hypothesis that the researcher proposes in this Class action research is "proven"